Prognostic Factors and Recurrence in Breast Cancer: Experience at the National Cancer Institute of Mexico. (5th July 2012) - Stankov, A.; Bargallo-Rocha, J. E.; Silvio, A. Ñamendys-Silva; Ramirez, M. T.; Stankova-Ninova, K.; Meneses-Garcia, A.
Abstract : The purpose of this study was to analyze the prognostic and predictive factors that relate to locoregional or distant recurrences in breast cancer patients who have been treated at the National Cancer Institute of Mexico. Multivariate, time-dependent Cox regression analyses indicate that the pN status (positive versus negative lymph node; P = 0.003 ; HR (hazard ratio), 3.47; CI (confidence interval), 1.52–7.91) and the pathological complete response of the patient to neoadjuvant chemotherapy (yes versus no; P = 0.061 ; HR, 0.38; CI, 0.14–1.04) were important prognostic factors for recurrence.